Case Assignment to Complements within Lexical Phrases: A Study Based on the Bahdini Sub-Dialect of Kurdish (Raparin Journal of Humanities (RJH), 2026)
This study uses Case Theory in the Government and Binding framework to explore the role of complements in lexical phrases within the Bahdini sub-dialect of Kurdish. Complements are essential elements in syntactic structures; In some phrases, they are obligatory, while in others, they are optional. Their presence and structure are essential at both syntactic and semantic degrees and fundamental to multiple branches of generative grammar.The research searches the case grading of complements to lexical leaders and extensive verbs, nouns, adjectives, and prepositions in Bahdini. The primary emphasis is on overt case form, including the accusative, which quality gender-specific markers in plural forms and abstract or unblemished cases. The study investigates the groups of complements that accept cases, the features of these cases, and the criteria for case tasks determined by the syntactic position and structure of both the complement and the lexical head. The result shows that not all lexical phrase complements in Bahdini have case marks. The allocation of cases varies by the phrase's internal structure and the element's grammatical function. The research utilizes a descriptive-analytical methodology, concentrating solely on the syntactic and semantic dimensions, employing data from naturally occurring language examples in Bahdini to validate the theoretical discourse.